2018
DOI: 10.1039/c8ra04013c
|View full text |Cite
|
Sign up to set email alerts
|

Application of hydrotalcite in soil immobilization of iodate (IO3)

Abstract: Radioactive iodine is quite mobile in soil and poses threats to human health and the ecosystem. Many materials, including layered double hydroxides (LDH), have been synthesized to successfully capture iodine from aqueous environments. However, limited information is available on the application of LDH in soil to immobilize iodine species. In the present study, the feasibility of using Mg-Al-NO 3 LDH for retention of soil iodate (IO 3 À ) in both batch and column systems was analyzed. , which was 28.6 times hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…shows the XRD patterns of the as-prepared host material. The peaks were attributed to the 00l, 01l and 11l series of Miller indices of a structure analogous to that of nitrate-containing LDHs (PDF# 35-0965) [50]. This result indicated that highly crystalline, single-phase lamellar LDH was obtained and that the interlamellar gallery was occupied by hydrated nitrate anions (d 003 = 0.890 nm).…”
Section: Characterization Of Ldh/antioxidant Compositesmentioning
confidence: 86%
“…shows the XRD patterns of the as-prepared host material. The peaks were attributed to the 00l, 01l and 11l series of Miller indices of a structure analogous to that of nitrate-containing LDHs (PDF# 35-0965) [50]. This result indicated that highly crystalline, single-phase lamellar LDH was obtained and that the interlamellar gallery was occupied by hydrated nitrate anions (d 003 = 0.890 nm).…”
Section: Characterization Of Ldh/antioxidant Compositesmentioning
confidence: 86%
“…, where M 2+ and M 3+ are metal ions located in octahedral positions of brucite-like layers, and A n− stands for inorganic or organic anions that compensate the positive charge of brucite-like layers [1,2]. The structural features of hydrotalcite-like compounds give them a number of specific ion-exchange [3][4][5], sorption [6][7][8], electrical [9][10][11], catalytic [12][13][14], and magnetic properties [15][16][17].…”
Section: Introductionmentioning
confidence: 99%